Pengaruh PLP, Persepsi Profesi Guru, dan Efikasi Diri terhadap Minat Menjadi Guru Dimoderasi oleh Lingkungan Keluarga pada Mahasiswa Pendidikan Ekonomi UNS - Meyliana Sekar Pangestu; Harini Harini; Salman Alfarisy Totalia (Departement of Mathematics Education, 2024)
This research aims to examine (1) the influence of Introduction to the Schooling Field (PLP) on interest in becoming a teacher, (2) the influence of perceptions of the teaching profession on interest in becoming a teacher, (3) the influence of self-efficacy on interest in becoming a teacher, (4) the influence of the family environment in moderating Introduction to the Schooling Field (PLP) on interest in becoming a teacher, (5) the influence of the family environment in moderating perceptions of the teaching profession on interest in becoming a teacher, and (6) the influence of the family environment in moderating self-efficacy on interest in becoming a teacher among FKIP UNS Economic Education students. The data collection method used was a questionnaire distributed via Google Form with a population of 118 students and a sample of 91 students. The sampling technique used is probability sampling technique and the type of sampling technique is proportionate random sampling. The analysis in this research uses MRA (Moderating Regression Analysis). Based on the test results, it was found that (1) Introduction to the Schooling Field (PLP) had no significant effect on interest in becoming a teacher, (2) Perception of the Teacher Profession had a negative and significant effect on interest in becoming a teacher, (3) Self-Efficacy had a positive and significant effect on interest in becoming teachers, (4) Family environment is not able to moderate Introduction to the Schooling Field towards interest in becoming a teacher, (5) Family environment is not able to moderate Teacher Professional Perceptions towards interest in becoming a teacher, and (6) Family environment is able to moderate Self-Efficacy towards interest in becoming a teacher. Therefore, the results of this research can be a benchmark for students to increase their interest in becoming a teacher.